2017
DOI: 10.1158/1541-7786.mcr-16-0350
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Sensing by TAM Receptors Regulates AKT-Dependent Chemoresistance and PD-L1 Expression

Abstract: Tyro3, Axl, and Mertk (collectively TAM receptors) are three homologous receptor tyrosine kinases that bind vitamin K-dependent endogenous ligands, Protein S (ProS), and growth arrest-specific factor 6 (Gas6), and act as bridging molecules to promote phosphatidylserine (PS)-mediated clearance of apoptotic cells (efferocytosis). TAM receptors are overexpressed in a vast array of tumor types, whereby the level of expression correlates with the tumor grade and the emergence of chemo- and radioresistance to target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 45 publications
(57 reference statements)
4
86
1
Order By: Relevance
“…Together, these studies suggest that antagonistic Mertk antibodies (via their role as PS receptors) may be attractive therapeutic targets in cancer (Figure 4).Moreover, analogous to the above-mentioned strategies to combine PS targeting antibodies anti-PD1 or anti-PDL1 antibodies, combinatorial strategies that combine TAM inhibitors with other checkpoint inhibitors may also be meritorious of further development. In support of this model, we have recently shown that PS (apoptotic cells) promotes TAM-mediated upregulation of PDL1 on several tumor cell lines 129. Further studies showing combined action of generalized TAM inhibitors with anti-PD1 in non-small cell lung cancer, or TAM inhibitors with anti-PD1 head and neck cancers supports this notion 130,131.…”
mentioning
confidence: 60%
“…Together, these studies suggest that antagonistic Mertk antibodies (via their role as PS receptors) may be attractive therapeutic targets in cancer (Figure 4).Moreover, analogous to the above-mentioned strategies to combine PS targeting antibodies anti-PD1 or anti-PDL1 antibodies, combinatorial strategies that combine TAM inhibitors with other checkpoint inhibitors may also be meritorious of further development. In support of this model, we have recently shown that PS (apoptotic cells) promotes TAM-mediated upregulation of PDL1 on several tumor cell lines 129. Further studies showing combined action of generalized TAM inhibitors with anti-PD1 in non-small cell lung cancer, or TAM inhibitors with anti-PD1 head and neck cancers supports this notion 130,131.…”
mentioning
confidence: 60%
“…Hence, the safety of MerTK-targeted therapies should be explored further. Several preclinical studies have reported similar adaptive responses caused by single TKI therapy, and co-targeting of the receptor tyrosine kinase family could, therefore, be a novel strategy for overcoming drug resistance and increasing efficacy [61,[121][122][123][124][125]. Notably, cells of the innate immune system are involved in the initiation and regulation of adaptive immune response.…”
Section: Tam Targetingmentioning
confidence: 99%
“…2d). It has been previously reported that many tumor cells and immunosuppressive cells within the TME upregulate the expression of receptor tyrosine kinases Tyro3, Axl, and Mertk (collectively known as TAM receptors), which can interact with PS to stimulate the expression of PD-L1 46 . Thus, our results further support the notion that PS may act akin or upstream of PD-L1, CTLA-4, TGF-β, and TIM-3, representing an important immune checkpoint to be targeted for enhancing the efficacy of antitumor immunotherapy.…”
Section: Cis Onlymentioning
confidence: 99%